Pengembangan Alat Peraga Pengukur Debit Air Menggunakan Sensor Flow Berbasis Arduino Sebagai Media Pembelajaran Fluida - Fita Tri Wahyuningsih; Yusro Al Hakim; Ashari Ashari (Universitas Muhammadiyah Purworejo, 2019)
Research has been carried out on the development of teaching aid for measuring water debit using an Arduino based flow sensor as a medium of fluid learning in order to determine the feasibility of a water discharge measuring instrument developed as a fluid learning media. This research is development research consisting of the stages of data collection, product design, design validity, design revision, limited trials. The research subjects for the limited trial were the 4th-semester students of the Physics Education Study Program, Muhammadiyah University Purworejo with 19 students. The product developed is a water discharge measuring device that uses an Arduino-based flow sensor as a fluid learning media through the validation stage by experts. Furthermore, the product is revised and limited to trial. From the results of the trial of the tool carried out the Water Discharge Gauge using an Arduino-based Flow Sensor obtained a debit of (3.80 ± 0.13) liters/minute. While the data from the test results taken manually were debit at (3.55 ± 0.31) liters/min. With a relative error that is very small, with a comparison of sensor and manual measurement data on water discharge of 3.40%. This shows the value of the measurement accuracy is very good. From the results of the validation carried out by the validator namely expert lecturers and peers, it was found that the quality of the teaching aids was included in the excellent category with an average percentage of 76% and the quality of the guidebook was included in the excellent category with an average percentage gain of 78%. A limited trial was conducted by conducting a practicum using a water discharge measuring instrument using an Arduino-based flow sensor, then the results of the student questionnaire responses resulted in a percentage value of 87.22% with very good criteria. Thus the Water Discharge Measuring Tool using Arduino Based Flow Sensors is feasible to be used in Fluid material experiments.